Oxygen ion conductor and preparation method thereof

CN119340437APending Publication Date: 2025-01-21CHANGCHUN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411448668.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

[0005]鉴于此,本发明提供了一种氧离子导体,旨在解决现有氧离子导体的导电率有限,且将原材料球磨混合后进行烧结的制备方法也会因原料混合不充分而导致成品整体质量低的问题

Benefits of technology

[0027] 1. In the present invention, Ba element and Sr element are doped into the existing NBT oxygen ion conductor. The joint doping of Ba and Sr can increase the oxygen vacancy concentration, thereby improving the ion conductivity of the material. The doping of Ba and Sr can help maintain or optimize the crystal structure, thereby increasing the mobility of oxygen; and the use of two doping elements will reduce the linear expansion coefficient of the material, improve its stability during thermal cycling, thereby reducing thermal stress. Damage caused by stress.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119340437A_ABST
    Figure CN119340437A_ABST
Patent Text Reader

Abstract

The invention relates to the field of oxygen ion conductors, in particular to an oxygen ion conductor and preparation thereof, the oxygen ion conductor is a Na0. 5B i0. 5T i0. 95-xBa0. 05Srx03 oxygen ion conductor, and the preparation method comprises the following steps: 1, configuring and mixing raw material powder according to a molar ratio, and then performing ultrasonic treatment; 2, adding an alcohol solution and acetic acid, and stirring to form gel; 3, drying and grinding the gel into powder; 4, adding a conductive additive and an adhesive for ball milling; 5, performing low-temperature drying after cold press molding; and 6, slowly cooling to room temperature after high-temperature sintering. According to the oxygen ion conductor prepared by the invention, the Sr element and the Ba element are doped into the original NBT oxygen ion conductor, so that the lattice structure of the material is changed, a large number of extra oxygen vacancies are introduced, the oxygen ion migration efficiency is improved, and the conductive efficiency is further greatly improved. Meanwhile, the raw materials are subjected to gel supporting and then grinding and sintering, so that the raw materials are fully fused, and the overall quality of the product is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of oxygen ion conductor materials, and in particular to an oxygen ion conductor and a preparation method thereof. Background Art

[0002] As global environmental problems become increasingly severe, people's environmental awareness is gradually improving. New energy sources are gradually replacing traditional energy sources such as oil and coal, becoming the main energy form for people's production and life. Among them, solid fuel cells (SOFCs) convert fuels (such as H2, CH4) and oxidants (such as O2 in the air) into electrical energy and thermal energy through electrochemical methods. Due to its high conversion efficiency, it can be used not only in industrial production, but also in fields such as automobiles and drones. A single fuel cell consists of a porous cathode, an anode and an electrolyte. The electrolyte material is the core part of the fuel cell. NBT oxygen ion conductors with ABO3 perovskite structure have high ionic conductivity and good stability at medium and low temperatures and are widely used in electrolyte materials for solid oxide fuel cells.

[0003] In order to further improve the ionic conductivity of oxygen ion conductors, ion doping is currently the most commonly used method. Existing oxygen ion conductors prepared by ion doping are generally doped with Sr elements, but doping with only one element has limited improvement in the conductivity of oxygen ion conductors, and the preparation method of ball-milling and mixing the raw materials and then sintering will also lead to the problem of low overall quality of the finished product due to insufficient mixing of the raw materials.

[0004] Therefore, developing an oxygen ion conductor with high conductivity and its preparation method has important practical significance. Summary of the invention

[0005] In view of this, the present invention provides an oxygen ion conductor, aiming to solve the problem that the conductivity of existing oxygen ion conductors is limited, and the preparation method of ball-milling and mixing raw materials and then sintering will also lead to low overall quality of the finished product due to insufficient mixing of raw materials.

[0006] In one aspect, the present invention provides an oxygen ion conductor having the molecular formula: Na 0.5 B i 0.5 T i 0.95- x Ba 0.05 Sr x 0 3 , where X is 0.01-0.03.

[0007] On the other hand, the present invention also provides a method for preparing the oxygen ion conductor, comprising:

[0008] S1, Na 2 C0 3、B i 2 0 3 、T i0 2 、BaCO 3 and SrCo 3 Mixing in a molar ratio of 0.5:0.5:0.95-X:0.0.5:X to obtain a first mixture;

[0009] S2, adding an alcohol solvent to the first mixture, stirring evenly, then performing ultrasonic treatment, and then adding acetic acid and continuing stirring until a gel is formed;

[0010] S3, drying the gel, and grinding the dried gel into powder to obtain gel powder;

[0011] S4, ball-milling the gel powder for 3-8 hours to mix evenly to obtain a second mixture;

[0012] S5, placing the second mixture into a mold for cold pressing and drying to obtain a molded conductor;

[0013] S6, sintering the formed conductor at a high temperature, and then slowly cooling it to room temperature to obtain the cationic conductor.

[0014] Preferably, the ball milling time is 5-8 hours, and further preferably, the ball milling time is 8 hours.

[0015] Furthermore, in step S4, a conductive additive and a binder are added to the gel powder before ball milling.

[0016] Furthermore, after the ultrasonic treatment is completed in step S1, the pH value of the solution needs to be detected in real time. When the acetic acid is added, stirring is performed while adding until the pH value of the solution is between 2-4, and then the stirring is continued until a gel is formed. During this period, the pH value of the solution is ensured to be maintained between 2-4 by adding the acetic acid at irregular intervals.

[0017] Furthermore, the alcohol solution is an ethanol solution, which is used to dissolve the first mixture.

[0018] Furthermore, in step S3, the gel is dried at low temperature, and the drying temperature is 70°C-100°C.

[0019] Preferably, the drying temperature is 70°C.

[0020] Furthermore, in step S4, 70-90 parts of the gel powder, 5-15 parts of the conductive additive, and 5-10 parts of the adhesive are added; the conductive additive is one of carbon black, activated carbon or polyethylene terephthalate; and the adhesive is one of polyvinyl alcohol, polyacrylamide or polyurethane.

[0021] Preferably, the conductive additive is carbon black, and the binder is polyvinyl alcohol.

[0022] Preferably, the gel powder is 80-90 parts, the conductive additive is 10-15 parts, and the adhesive is 8-10 parts; more preferably, the gel powder is 90 parts, the conductive additive is 15 parts, and the adhesive is 10 parts.

[0023] Furthermore, the pressure during the cold press molding is 100-200 MPa, the molding time is 1 minute, and the molding is maintained for 6 hours.

[0024] Furthermore, in step S5, low temperature drying is adopted, and the temperature is 60°C-80°C.

[0025] Furthermore, in step S6, the high temperature sintering temperature is 800° C.-1000° C., and the sintering time is 1.5 hours.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] 1. The present invention doped Ba and Sr elements into the existing NBT oxygen ion conductor. The co-doping of Ba and Sr can increase the oxygen vacancy concentration, thereby improving the ionic conductivity of the material. The doping of Ba and Sr can help maintain or optimize the crystal structure, thereby increasing the mobility of oxygen; and the use of two doping elements can reduce the linear expansion coefficient of the material, improve its stability during thermal cycling, and thus reduce the damage caused by thermal stress.

[0028] 2. The present invention adopts a preparation method of first preparing the raw materials into gel and then drying, grinding, pressing and sintering the gel, so that the raw materials can be evenly mixed, ensuring the uniform doping of Ba and Sr elements and avoiding the uneven composition that may occur in the solid phase sintering method; at the same time, the gel method will pre-generate smaller particles, which can effectively reduce the temperature and time required for sintering; and the gel method can obtain nanometer-scale particles, which can significantly increase the specific surface area of ​​the material, help to improve the reactivity and conductivity of the material, and small particles will also combine together faster during sintering.

[0029] 3. The present invention improves the overall conductivity of the oxygen ion conductor by adding conductive additives during the preparation process.

[0030] 4. The present invention adds a binder during the preparation process to make different particles more closely bonded, thereby improving the mechanical strength and durability of the oxygen ion conductor and reducing the risk of brittle fracture of the material during operation. At the same time, the binder helps to maintain the shape of the powder during the molding process, especially during cold pressing, making the preparation process of the oxygen ion conductor smoother. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Various other advantages and benefits will become apparent to those of ordinary skill in the art by reading the detailed description of the preferred embodiments below. The accompanying drawings are only for the purpose of illustrating the preferred embodiments and are not to be considered as limiting the present invention. Moreover, the same reference symbols are used throughout the accompanying drawings to represent the same components. In the accompanying drawings:

[0032] Figure 1 This is a flow chart for preparing an oxygen ion conductor provided in an embodiment of the present invention. DETAILED DESCRIPTION

[0033] Exemplary embodiments of the present disclosure will be described in more detail below with reference to the accompanying drawings. Although exemplary embodiments of the present disclosure are shown in the accompanying drawings, it should be understood that the present disclosure can be implemented in various forms and should not be limited by the embodiments described herein. On the contrary, these embodiments are provided in order to enable a more thorough understanding of the present disclosure and to fully convey the scope of the present disclosure to those skilled in the art. It should be noted that, in the absence of conflict, the embodiments of the present invention and the features described in the embodiments can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.

[0034] As new energy sources gradually replace traditional energy sources such as oil and coal, they become the main energy form for people's production and life. Among them, solid fuel cells (SOFC) convert fuels (such as H2, CH4) and oxidants (such as O2 in the air) into electrical energy and thermal energy through electrochemical methods. Due to its high conversion efficiency, it can be used not only in industrial production, but also in fields such as automobiles and drones. A single fuel cell consists of a porous cathode, an anode and an electrolyte. The electrolyte material is the core part of the fuel cell. Therefore, NBT oxygen ion conductors with ABO3 perovskite structure have high ionic conductivity and good stability at medium and low temperatures and are widely used in electrolyte materials for solid oxide fuel cells. In order to further improve the ionic conductivity of oxygen ion conductors, doping modification by ion doping is currently the most commonly used method. Existing oxygen ion conductors prepared by ion doping are generally doped with Sr elements, but doping with only one element has limited improvement in the conductivity of oxygen ion conductors, and the preparation method of ball milling and mixing the raw materials and then sintering them will also lead to the problem of low overall quality of the finished product due to insufficient mixing of the raw materials.

[0035] The present invention provides an oxygen ion conductor, the molecular formula of which is: Na 0.5 Bi 0.5 T i 0.95-x Ba 0.05 Sr x 0 3 , where X is 0.01-0.03.

[0036] Specifically, the present invention doped Ba and Sr elements into the original NBT oxygen ion conductor to prepare a new type of oxygen ion conductor material.

[0037] It is understandable that the co-doping of Ba and Sr can increase the oxygen vacancy concentration, thereby improving the ionic conductivity of the material. The doping of Ba and Sr can help maintain and optimize the crystal structure, thereby increasing the mobility of oxygen; and the use of two doping elements will reduce the linear expansion coefficient of the material, improve its stability during thermal cycling, and thus reduce the damage caused by thermal stress.

[0038] See also Figure 1 As shown, the method for preparing an oxygen ion conductor provided by an embodiment of the present invention comprises:

[0039] S1, Na 2 C0 3 、B i 2 0 3 、T i0 2 、BaCO 3 and SrCo 3 Mixing in a molar ratio of 0.5:0.5:0.95-X:0.05:X to obtain a first mixture;

[0040] S2, adding an alcohol solvent to the first mixture, stirring evenly, then performing ultrasonic treatment, and then adding acetic acid and continuing stirring until a gel is formed;

[0041] S3, drying the gel, and grinding the dried gel into powder to obtain gel powder;

[0042] S4, ball-milling the gel powder for 3-8 hours to mix evenly to obtain a second mixture;

[0043] S5, placing the second mixture into a mold for cold pressing and drying to obtain a molded conductor;

[0044] S6, sintering the formed conductor at a high temperature, and then slowly cooling it to room temperature to obtain the cationic conductor.

[0045] Specifically, the value of X is between 0.01 and 0.03. 2 C0 3 、B i 2 0 3 、T i0 2 、BaCO 3 And SrCo3 are all ultrafine powders with a purity greater than 99%.

[0046] Specifically, the first mixture is placed in a container, and then an alcohol solution is added and stirred into a slurry, and then ultrasonic treatment is performed so that the first mixture can be fully dissolved.

[0047] It can be understood that the preparation method of preparing the raw materials into a gel, and then drying, grinding, pressing and sintering the gel allows the raw materials to be evenly mixed at the molecular level, thereby ensuring the consistency of the composition, ensuring the uniform doping of the Ba and Sr elements, and avoiding the uneven composition that may occur in the solid-phase sintering method; at the same time, the gel method will pre-generate smaller particles, which can effectively reduce the temperature and time required for sintering; and the gel method can obtain nanoscale particles, which can significantly increase the specific surface area of ​​the material, help to improve the reactivity and conductivity of the material, and small particles can also combine together faster during sintering.

[0048] In the present invention, before ball-milling the gel powder in step S4, a conductive additive and an adhesive are added, and the gel powder is 70-90 parts, the conductive additive is 5-15 parts, and the adhesive is 5-10 parts; the gel powder, the conductive additive and the adhesive are preferably 80-90 parts of gel powder, 10-15 parts of conductive additive, and 8-10 parts of adhesive; further preferably, the gel powder is 90 parts, the conductive additive is 15 parts, and the adhesive is 10 parts.

[0049] The conductive additive is one of carbon black, activated carbon or polyethylene terephthalate; the adhesive is one of polyvinyl alcohol, polyacrylamide or polyurethane. The conductive additive is preferably carbon black; the adhesive is preferably polyvinyl alcohol.

[0050] It can be understood that the addition of conductive additives during the preparation process improves the overall conductivity of the oxygen ion conductor; the addition of binders during the preparation process will make the different particles more closely combined, thereby improving the mechanical strength and durability of the oxygen ion conductor and reducing the risk of brittle fracture of the material during operation. At the same time, the binder helps to maintain the shape of the powder during the molding process, especially during cold pressing, making the electrode preparation process smoother.

[0051] In the present invention, the alcohol solution used in step S2 is an ethanol solution, which is used to dissolve the first mixture to prepare a gel.

[0052] In the present invention, after the ultrasonic treatment in step S1 is completed, the pH value of the solution needs to be detected in real time. When acetic acid is added, stirring is performed while adding until the pH value of the solution is between 2 and 4, and then the addition is stopped. Then, while continuing to stir, acetic acid is added dropwise at irregular intervals according to the detected pH value to ensure that the pH value of the solution is always between 2 and 4 until a gel is formed.

[0053] It is understandable that gel will only form when the pH value is between 2-4.

[0054] In the present invention, the gel is dried at low temperature in step S3, and the drying temperature is 70°C-100°C, and the drying temperature is preferably 70°C.

[0055] In the present invention, the pressure during the cold press molding is 100-200 MPa, the molding time is 1 minute, and the molding is maintained for 6 hours; the pressure during the cold press molding is preferably 200 MPa.

[0056] It is understandable that drying and sintering are not performed immediately after pressing and forming, but are first kept for 6 hours, which can effectively prevent cracking and breakage caused by loose pressing of the formed conductor during drying or high-temperature sintering.

[0057] In the present invention, the drying in step S5 is carried out by low-temperature drying at a temperature of 60°C-80°C, preferably 80°C.

[0058] In the present invention, the high temperature sintering temperature in step S6 is 800° C.-1000° C., preferably 1000° C., and the sintering time is 1.5 hours.

[0059] Example 1

[0060] 1. Put Na 2 C0 3 、Bi 2 0 3 、T i 0 2 、BaCO 3 and SrCo 3 Mixing in a molar ratio of 0.5:0.5:0.85:0.05:0.01 to obtain a first mixture;

[0061] 2. Add ethanol solvent to the first mixture, stir evenly, and then perform ultrasonic treatment, then add acetic acid to ensure that the pH value of the solution is between 2-4, and continue stirring until a gel is formed;

[0062] 3. Drying the gel at a temperature of 70° C., and grinding the dried gel into powder to obtain gel powder;

[0063] 4. Mix 90 parts of gel powder, 15 parts of carbon black and 10 parts of polyvinyl alcohol and ball mill for 8 hours to obtain a second mixture;

[0064] 5. Place the second mixture into a mold for cold pressing at a pressure of 200 MPa for 1 minute. After molding, keep it for 6 hours and then perform low-temperature drying at 60°C.

[0065] 6. The formed conductor is sintered at a high temperature of 1000° C. for 1.5 hours, and then slowly cooled to room temperature to obtain the oxygen ion conductor.

[0066] Example 2

[0067] 1. Put Na 2 C0 3 、Bi 2 0 3 、T i 0 2 、BaCO 3 and SrCo 3 Mixing in a molar ratio of 0.5:0.5:0.75:0.05:0.02 to obtain a first mixture;

[0068] 2. Add ethanol solvent to the first mixture, stir evenly, and then perform ultrasonic treatment, then add acetic acid to ensure that the pH value of the solution is between 2-4, and continue stirring until a gel is formed;

[0069] 3. Drying the gel at a temperature of 70° C., and grinding the dried gel into powder to obtain gel powder;

[0070] 4. Mix 90 parts of gel powder, 15 parts of carbon black and 10 parts of polyvinyl alcohol and ball mill for 8 hours to obtain a second mixture;

[0071] 5. Place the second mixture into a mold for cold pressing at a pressure of 200 MPa for 1 minute. After molding, keep it for 6 hours and then perform low-temperature drying at 60°C.

[0072] 6. The formed conductor is sintered at a high temperature of 1000° C. for 1.5 hours, and then slowly cooled to room temperature to obtain the oxygen ion conductor.

[0073] Example 3

[0074] 1. Put Na 2 C0 3 、Bi 2 0 3 、T i 0 2 、BaCO 3 and SrCo 3 Mixing in a molar ratio of 0.5:0.5:0.65:0.05:0.03 to obtain a first mixture;

[0075] 2. Add ethanol solvent to the first mixture, stir evenly, and then perform ultrasonic treatment, then add acetic acid to ensure that the pH value of the solution is between 2-4, and continue stirring until a gel is formed;

[0076] 3. Drying the gel at a temperature of 70° C., and grinding the dried gel into powder to obtain gel powder;

[0077] 4. Mix 90 parts of gel powder, 15 parts of carbon black and 10 parts of polyvinyl alcohol and ball mill for 8 hours to obtain a second mixture;

[0078] 5. Place the second mixture into a mold for cold pressing at a pressure of 200 MPa for 1 minute. After molding, keep it for 6 hours and then perform low-temperature drying at 60°C.

[0079] 6. The formed conductor is sintered at a high temperature of 1000° C. for 1.5 hours, and then slowly cooled to room temperature to obtain the oxygen ion conductor.

[0080] Example 4

[0081] 1. Put Na 2 C0 3 、Bi 2 0 3 、T i 0 2 、BaCO 3 and SrCo 3 Mixing in a molar ratio of 0.5:0.5:0.65:0.05:0.03 to obtain a first mixture;

[0082] 2. Add ethanol solvent to the first mixture, then perform ultrasonic treatment, stir evenly, then add acetic acid to ensure that the pH value of the solution is between 2-4, and continue stirring until a gel is formed;

[0083] 3. Drying the gel at a temperature of 100° C., and grinding the dried gel into powder to obtain gel powder;

[0084] 4. Mix 70 parts of gel powder, 15 parts of carbon black and 10 parts of polyvinyl alcohol and ball mill for 3 hours to obtain a second mixture;

[0085] 5. Place the second mixture into a mold for cold pressing at a pressure of 100 MPa for 1 minute, keep it for 6 hours after molding, and then perform low-temperature drying at 80°C;

[0086] 6. The formed conductor is sintered at a high temperature of 800° C. for 1.5 hours, and then slowly cooled to room temperature to obtain the oxygen ion conductor.

[0087] Those skilled in the art will appreciate that the embodiments of the present application may be provided as methods, systems or computer program products. Therefore, the present application may adopt the form of a complete hardware embodiment, a complete software embodiment, or an embodiment in combination with software and hardware. Moreover, the present application may adopt the form of a computer program product implemented on one or more computer-usable storage media (including but not limited to disk storage, CD-ROM, optical storage, etc.) containing computer-usable program codes.

[0088] The present application is described with reference to flowcharts and / or block diagrams of methods, devices (systems) and computer program products according to embodiments of the present application. It should be understood that each process and / or box in the flowchart and / or block diagram, as well as the combination of processes and / or boxes in the flowchart and / or block diagram, can be implemented by computer program instructions. These computer program instructions can be provided to a processor of a general-purpose computer, a special-purpose computer, an embedded processor or other programmable data processing device to generate a machine, so that the instructions executed by the processor of the computer or other programmable data processing device generate instructions for implementing the processes in the flowchart and / or block diagram. Figure 1 A process or multiple processes and / or boxes Figure 1 A device that provides the functions specified in a block or multiple blocks.

[0089] These computer program instructions may also be stored in a computer-readable memory capable of directing a computer or other programmable data processing device to operate in a specific manner, so that the instructions stored in the computer-readable memory produce an article of manufacture comprising an instruction device, which implements the process Figure 1 A process or multiple processes and / or boxes Figure 1 A function specified in one or more boxes.

[0090] These computer program instructions can also be loaded onto a computer or other programmable data processing device so that a series of operating steps are executed on the computer or other programmable device to produce a computer-implemented process, thereby providing instructions for implementing the process. Figure 1 A process or multiple processes and / or boxes Figure 1 The steps for the functions specified in one or more boxes.

[0091] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the specific implementation methods of the present invention can still be modified or replaced by equivalents. Any modification or equivalent replacement that does not depart from the spirit and scope of the present invention should be covered within the scope of protection of the claims of the present invention.

Claims

1. An oxygen ion conductor, characterized in that Molecular formula: Na 0.5 Bi 0.5 Ti 0.95-x Ba 0.05 Sr x 03, where X is 0.01-0.

03.

2. The method for preparing an oxygen ion conductor according to claim 1, characterized in that: include: S1. Mix Na2C03, Bi2O3, TiO2, BaCO3 and SrCo3 in a molar ratio of 0.5:0.5:0.95-X:0.05:X to obtain a first mixture; S2, adding an alcohol solvent to the first mixture, stirring evenly, then performing ultrasonic treatment, and then adding acetic acid and continuing stirring until a gel is formed; S3, drying the gel, and grinding the dried gel into powder to obtain gel powder; S4, ball-milling the gel powder for 3-8 hours to mix evenly to obtain a second mixture; S5, placing the second mixture into a mold for cold pressing and drying to obtain a molded conductor; S6, sintering the formed conductor at a high temperature, and then slowly cooling it to room temperature to obtain the cationic conductor.

3. The method for preparing an oxygen ion conductor according to claim 2, characterized in that: In step S4, a conductive additive and a binder are added to the gel powder before ball milling.

4. The method for preparing an oxygen ion conductor according to claim 2, characterized in that: After the ultrasonic treatment in step S2, the pH value of the solution is detected in real time, and the acetic acid is added while stirring until the pH value of the solution is between 2-4 and then the addition is stopped, and then stirring is continued until a gel is formed. During this period, the pH value of the solution is ensured to be maintained between 2-4 by adding acetic acid at irregular intervals.

5. The method for preparing an oxygen ion conductor according to claim 2, characterized in that: The alcohol solution is an ethanol solution, which is used to dissolve the first mixture.

6. The method for preparing an oxygen ion conductor according to claim 2, characterized in that: In step S3, the gel is dried at low temperature, and the drying temperature is 70°C-100°C.

7. The method for preparing an oxygen ion conductor according to claim 3, characterized in that: In step S4, the gel powder is 70-90 parts, the conductive additive is 5-15 parts, and the adhesive is 5-10 parts; the conductive additive is one of carbon black, activated carbon or polyethylene terephthalate; the adhesive is one of polyvinyl alcohol, polyacrylamide or polyurethane.

8. The method for preparing an oxygen ion conductor according to claim 2, characterized in that: The pressure during the cold pressing is 100-200 MPa, the molding time is 1 minute, and the molding is maintained for 6 hours.

9. The method for preparing an oxygen ion conductor according to claim 2, characterized in that: In step S5, the drying is carried out at low temperature, and the temperature is 60°C-80°C.

10. The method for preparing an oxygen ion conductor according to claim 2, characterized in that: The high temperature sintering temperature in step S6 is 800° C.-1000° C., and the sintering time is 1.5 hours.